Sustainable Development Transformation of the Republic of Armenia: Context and Perception - Sargsyan, Hayk; Gevorgyan, Ruben; Kochinyan, Narine; Sargsyan, Sona (Bulletin of Yerevan University G: Economics, 2024)
The article reveals the need for and methodology of the transformation of the sustainable development index. The idea of transforming the index made up of the indicators established by the UN’s Sustainable Development Agenda was proposed due to the most acute manifestations of certain regional problems. As for the Republic of Armenia, those issues also include security and overcoming the constitutional deficit in addition to socio-economic and ecological problems. Methodologically, this approach allowed us to elaborate a new set of sustainable development indicators. Due to the introduced set of indicators, the sustainable development index (SDG Index Score -Y) is linked with variables such as the capital and labor - K, L, the ecological component (Ecology - E), the level of constitutionalism (Constitutional Compliance - U), security (Security - S), and time - T. In the proposed concept, the optimal operation of sustainable development (OOSD) derives from the goals and limitations determined by the specifics of development. By virtue of the indicators given above, we will have the sustainable development index modified as follows: Y=(K,L,E,U,S,T). The schematic diagram of the concept includes indicators of sustainable development that relate to the responsible institutions of management, and indicate the respective norm required by the Constitution. The optimal management model is formulated based on the developed conceptual basis, where is required to select such a management that move the object from one state of stability to another, where the objective function takes the optimal value specified for the limitations of sustainable development indicators.